The sound recording and archive from the standpoints of ethnomusicology - García, Miguel A. (Revista General de Información y Documentación, 2019)
The article proposes a journey along the different ways in which ethnomusicology has reflected on the sound recording and archive, from its first formulation, known as comparative musicology, to the present day. The journey reveals that the discipline has selectively adopted questions, definitions and concepts from other areas of knowledge, and that its reflections on the sound recording and archive have been sensitive to the theoretical, ethical and methodological changes, which have taken place inside the discipline. It also confirms that in the current reflection scenario on the subject very different perspectives coexist, some of them adopted over a century ago, which define the archive as an institution, reservoir, memory and/or knowledge.